2011
DOI: 10.1097/iae.0b013e3181ff0d5a
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in Intraocular Pressure After Pars Plana Vitrectomy

Abstract: In this series, vitrectomy does not appear to increase IOP even after removal of the crystalline lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 27 publications
2
42
1
7
Order By: Relevance
“…Subsequently, this traction on the ciliary body can also cause a cyclodialysis cleft [8]. Similar results were found after PPV without SOI [17], where pseudophakic diabetic patients developed less ocular hypertension than nondiabetic patients. This observation was attributed to the fact that diabetic eyes exhibit more ischemia, and have a lower rate of oxygen reaching the trabecular meshwork, and hence lower oxidative stress than nondiabetic eyes.…”
Section: Discussionsupporting
confidence: 74%
“…Subsequently, this traction on the ciliary body can also cause a cyclodialysis cleft [8]. Similar results were found after PPV without SOI [17], where pseudophakic diabetic patients developed less ocular hypertension than nondiabetic patients. This observation was attributed to the fact that diabetic eyes exhibit more ischemia, and have a lower rate of oxygen reaching the trabecular meshwork, and hence lower oxidative stress than nondiabetic eyes.…”
Section: Discussionsupporting
confidence: 74%
“…37 Perhaps for similar reasons, eyes that had undergone pars plana vitrectomy for indications other than retinal detachment were also two and half times more likely to develop OHT, a finding that is similar to two other studies reporting on the increased risk of open angle glaucoma after vitrectomy. 3840 Lower vision, need for cataract surgery, and need for vitrectomy likely all serve as indicators for more severe disease and thus higher risk of IOP elevation; hypotony may reflect extreme disease severity with ciliary body damage explaining the association with hypotony as well as OHT in this cohort. As expected, the presence of peripheral anterior synechiae (PAS) almost doubled the risk of developing OHT≥30 mmHg; a third of eyes which had evidence of PAS recorded by chart review developed OHT at 2 years.…”
Section: Discussionmentioning
confidence: 94%
“…Although these data did not reach statistical significance, it was pointed out that because the data were nearly statistically significant, enrolling a larger number of patients would probably reveal the risk of glaucoma after these surgeries [21]. In another study, after a mean follow-up of two years, no evidence of increased risk of OHT or OAG was detected, even in pseudophakic patients [22]. Chang and Smith [21] concluded that it is necessary to collect more long-term data to better assess this risk.…”
Section: Vitrectomy Cataract and Glaucomamentioning
confidence: 92%